1999
DOI: 10.1021/jo981042x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Spectroscopic Studies Related to the Lewis Acidity of Lithium Perchlorate in Diethyl Ether

Abstract: Polarimetric studies on camphor (2) as well as IR studies on crotonaldehyde (CA; 1) and benzonitrile (BN; 3) confirm the conclusion of a previously published NMR study on crotonaldehyde that lithium perchlorate (LP) weakly binds to probe bases in diethyl ether (DE). The weak binding is a consequence of the fact that the lithium ion (actually the LP ion pair and higher aggregates), a powerful Lewis acid in the gas phase, competitively binds to ether and the added base. Methylene camphor (5), (E)-1,3-pentadiene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Lithium perchlorate solutions can be considered as highly polar media 12–15. A summary of its remarkable effects was collected in several reviews 15, 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium perchlorate solutions can be considered as highly polar media 12–15. A summary of its remarkable effects was collected in several reviews 15, 16…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that the effect of lithium perchlorate solution in diethyl ether (LPDE) was caused by electrostatic stabilization of the charged static or dynamic states 12–14. Other authors15, 16 considered the rate acceleration in LP solutions as a result of the Lewis acidity of LP. The opposite effects of LP in diethyl ether (DE) on the rate constants of the forward and back reactions and the sharp increase in the equilibrium constant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[16] According to Kabalka and co-workers, based on spectroscopic and chemical evidence, the increased rates of reaction of certain DielsϪAlder reactions and high selectivities are due to the mild Lewis acidity of the lithium ion in ether. [17] According to these authors, the strong and intrinsic Lewis acidity of lithium ion is moderated in diethyl ether due to its complexation with the solvent and the counter ion. Forman and Dailey, [18] and Righetti and co-workers, [19] have also shown that the rate enhancement of DielsϪAlder reactions is due to Lewis acid catalysis by the lithium ion.…”
Section: Nature Of the Lithium Perchlorate/diethyl Ether Mediummentioning
confidence: 99%
“…Diethyl ether is a coordinating solvent (n-donor) and the coordination of the lithium ion to the lone pair of oxygen in ether moderates the Lewis acidity of the lithium ion. [17,20] Although the moderated Lewis acidity of the lithium ion is useful in effecting very selective synthetic transformations, some reactions fail to proceed in LPDE due to the weak Lewis acidity of the lithium ion. For example, the aldol and Michael reactions of silyl enol ethers with aldehydes and ketones failed to proceed in 5  LPDE medium (Scheme 13, reaction 23).…”
Section: A Comparison Of Lithium Perchlorate In Diethyl Ether and Nitmentioning
confidence: 99%
“…These unusual rate enhancements have been attributed to electrostatic catalysis in which the large Coulomb fields of the ions stabilise polar transition states and much of these data can be rationalised by mechanisms in which lithium ion functions as a Lewis acid catalyst. 22 Thus, we planned to exploit the electrostatic catalytic effect of ion aggregates in metal perchlorates and were delighted to see the recent report of use of LiClO 4 as acylation catalyst. 23 The role of metal perchlorates in activating the anhydride may be explained in Figure 1.…”
mentioning
confidence: 99%